Agricultural digital plot: Capacity building for innovation in Guatemala’s dry corridor - Ramos, Gresia Dalal; Jimenez, Daniel Ricardo; Lizarazo, Miguel; Martinez, Jesus David; Bonilla, Melissa; Estrada Vargas, Oscar; Munoz, Luis Armando (2024)
The CGIAR Digital Innovation Initiative, together with AgriLAC, has pioneered the promotion of agricultural technologies in Guatemala, working closely with key local partners, the Chort’i Regional Peasant Association (ASORECH) and the Centro Universitario de Oriente (CUNORI). Together, they have created a space for learning, exploration, and technology validation focused on the agri-food sector in Chiquimula, one of the most vulnerable departments in Guatemala’s Dry Corridor. Known as the Agricultural Digital Plot, this space has functioned as an innovative platform at CUNORI, facilitating interaction and knowledge exchange among local farmers, ASORECH technicians, and CUNORI students and faculty, thereby strengthening capacity in the use of agricultural technologies. Each agro-climatic sensor and component of the Digital Plot was installed to validate its use in the local context and provide recommendations to users, with the aim of building trust in these technologies and fostering informed decision-making. As a result, the Digital Plot has become the only dedicated space in Chiquimula for integrating advanced technologies to support the agri-food sector. The experiences and results achieved have also drawn the attention of international institutions. The Digital Plot’s success has attracted interest from universities in the region, including La Molina Agrarian University in Peru and Universidad Zamorano in Honduras. While La Molina explores its potential in Peru, Zamorano aims to replicate the model in the Dry Corridor of Honduras, learning from the similar experience in Guatemala’s Dry Corridor. This growing international interest underscores the potential of the Digital Plot as a benchmark for agricultural modernization in other regions around the world.